2002
DOI: 10.1123/mcj.6.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Multi-Joint Performance with Age

Abstract: The purpose of this study was to determine whether elderly adults exhibit deficits in the performance of multi-joint movements. Two groups of subjects (mean ages 68.9, 30.1 years respectively) participated in this experiment. Subjects performed planar arm pointing movements to various targets. One target could be achieved via elbow extension only, while the remaining three required both elbow extension and horizontal shoulder flexion, thus requiring coordination at the two joints. In contrast to the young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 29 publications
8
102
1
1
Order By: Relevance
“…It is well known that aging affects human skeletal muscle structure, which, in turn, may influence muscle contraction properties in elderly people [32,46,47]. This sarcopenia, associated to neural factors, notably to the reduction in motor unit activation capacity [17,49] and to the coactivation of antagonist muscles [23,43], may account for the loss of muscle strength and power in elderly people. However, these structural and neural factors alone cannot fully explain the decline of movement speed which accompanies normal aging.…”
Section: Overt Movement Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that aging affects human skeletal muscle structure, which, in turn, may influence muscle contraction properties in elderly people [32,46,47]. This sarcopenia, associated to neural factors, notably to the reduction in motor unit activation capacity [17,49] and to the coactivation of antagonist muscles [23,43], may account for the loss of muscle strength and power in elderly people. However, these structural and neural factors alone cannot fully explain the decline of movement speed which accompanies normal aging.…”
Section: Overt Movement Executionmentioning
confidence: 99%
“…Is this ability function of the kind and difficulty of motor task being imagined? It is well known that normal aging influences cognitive functions [2,13,24,40,41] and sensorimotor control of actions [22,43,44]. The state of musculoskeletal system, in particular that of muscular mechanics and structure, is also modified [17,23,26,32,46,47,49].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on rapid goal-directed arm movements found older adults to show slower and more variable arm movements than younger adults (Darling et al, 1989;Yan et al, 1998Yan et al, , 2000 and higher levels of muscle coactivation . Moreover, agerelated impairments in movement smoothness and end-point accuracy are generally more pronounced for movements requiring shoulder-elbow coordination than for single-joint actions (Seidler et al, 2002), suggesting a selective deficit in multijoint coordination among the elderly.…”
Section: Introductionmentioning
confidence: 98%
“…This decrease has a physiologic basis in aging and is amplified by disuse and dysfunction. In general, aging adults demonstrate decreases in movement speed (Light, 1990;Mankovsky, Mints, & Lisenyuk, 1982;Poston et al, 2008;Yan et al, 1998), accuracy of movement (Chaput & Proteau, 1996), reaction time (Light, 1990;Sparrow et al, 2006;Yan et al, 1998), strength (Roos et al, 1997;Vandervoort, 2002), hand dexterity (Contreras-Vidal, Teulings, & Stelmach, 1998;Seidler, Alberts, & Stelmach, 2002), and postural control (Jonsson, Henriksson, & Hirschfeld, 2007;Koceja, Allway, & Earles, 1999;Mourey et al, 1998;. En masse, these changes have the potential to contribute to a spiral of disuse and loss of function that often characterizes the process of aging.…”
Section: Changes To the Human Sensorimotor System Across The Lifespanmentioning
confidence: 99%